Biogas power plant in kalipucang hamlet, bangunjiwo village, kasihan district, bantul regency - Muhammad Abdus Shomad; Sotya Anggoro (Peneliti Teknologi Teknik Indonesia, 2021)
Kalipucang hamlet is in Bangunjiwo Village and is home to 53 farmers from the “Andini Makmur” livestock farming group. The majority of the population works as cattle breeders, while others are farmers. The livestock farming group